2015
DOI: 10.1111/cea.12595
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aspergillus sensitization and allergic bronchopulmonary aspergillosis in cystic fibrosis: systematic review and meta‐analysis

Abstract: There is a high prevalence of AS and ABPA in patients with CF. Despite six decades of research, there is still a need to adopt uniform methodology and criteria for the diagnosis of AS/ABPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
111
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 79 publications
3
111
0
11
Order By: Relevance
“…A majority of ABPA patients have symptoms of asthma, a common disease, so the rate of misdiagnosis could be 3.7–11.1% [4]. The overall prevalence of ABPA in patients with cystic fibrosis has been estimated at nearly 9% [5]. In 2013, the recommended diagnostic guidelines for ABPA were put forward by the ABPA expert group of the International Society for Human and Animal Mycology (ISHAM).…”
Section: Introductionmentioning
confidence: 99%
“…A majority of ABPA patients have symptoms of asthma, a common disease, so the rate of misdiagnosis could be 3.7–11.1% [4]. The overall prevalence of ABPA in patients with cystic fibrosis has been estimated at nearly 9% [5]. In 2013, the recommended diagnostic guidelines for ABPA were put forward by the ABPA expert group of the International Society for Human and Animal Mycology (ISHAM).…”
Section: Introductionmentioning
confidence: 99%
“…There are an estimated 3 million individuals with chronic PA and 4.5 million with allergic bronchopulmonary aspergillosis globally (10,11). Af has also been implicated in the pathogenesis of asthma, chronic obstructive airways disease, and bronchiectasis (11)(12)(13). Treatment options remain limited, and high mortality rates persist (14).…”
mentioning
confidence: 99%
“…Recently, differences have been identified that might enable a relatively simple differentiation between ABPA and AS based on the determination of CDC203c basophils concentration, galactomannan antigen in lower respiratory tract samples and pecific IgG in serum. In contrast with ABPA patients, patients with AS have a lower plasma concentration of CDC203c basophils, a negative galactomannan test (< 0.5) and a positive A.fumigatus-specific serum IgG (< 75µg/ mL) (13,16,27).…”
Section: Fungi Of the Genus Aspergillusmentioning
confidence: 98%
“…This term is used to describe hypersensitity reactions which do not meet all of the criteria necessary for making a diagnosis of ABPA (17). AS supposedly affects between 20 and 65 % of CF patients (16). The problems of establishing the prevalence of AS lie in its overlapping clinical features with ABPA and the use of different diagnostic microbiological methods.…”
Section: Fungi Of the Genus Aspergillusmentioning
confidence: 99%
See 1 more Smart Citation